The Girl on the Train: Analisis Habitus dan Selera Penonton dalam Film Psychological Thriller: The Girl on the Train: Questioning Habitus and Taste of the Audience on Psychological Thriller Film - Sulistyaningtyas Sulistyaningtyas (Balai Bahasa Provinsi Papua, 2019)
The taste of film is a reflection of the social, economic, and political circumstances in a certain period in history. Taste, as subjective preferences towards symbolic objects, is strongly determined by the habitus of the audience. This study is motivated by the audience’s interest to psychological thriller film, which is questionable given that this genre drives them to experience a set of negative emotions. To examine the research problems, this study adopts a Bourdieu perspective related to habitus and taste. The objective of this study is to find out the interrelation of habitus and taste of the audience in affecting their attraction towards the psychological thriller film. To give a specific context in the analysis process, The Girl on the Train film is chosen as the material object of this study. By using qualitative research methods, the results show that the habitus of the present conditions is engaged in a confrontation of social conflicts. It drives the audience to construct their taste of psychological thriller film as an escape from reality. Though this genre gives a set of detrimental feelings to the audience, they gain satisfaction as they play an important role in solving the problems of the film.